2008
DOI: 10.1016/j.vaccine.2008.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Nef modulates the immunogenicity of Gag encoded in a non-infectious HIV DNA vaccine

Abstract: Gag-CD8+ T cell responses are associated with immune control of HIV infection. Since during HIV infection Nef impairs T cell responses, we evaluated whether deletion of nef from a non-infectious HIV DNA vaccine (Delta4 Nef+), creating Delta5 Nef(-), would affect its immunogenicity. When compared with Delta4, mice injected with Delta5 developed significantly lower CD8+ T cell responses to Gag, but no significant change in the responses to Env was observed. In vitro, deletion of Nef abrogated the induced cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Since this is the first description of the use of a high dose of HIV DNA vaccine in NHP, we examined these two issues. In our recently published data, we clearly demonstrated that the great majority of primary cells transfected by our ⌬4SHIV KU2 DNA vaccine underwent apoptosis following the expression of viral proteins (4). Assuming that this mechanism also occurs in cells express- VOL.…”
Section: Fig 6 Hiv-specific Cd4mentioning
confidence: 65%
See 2 more Smart Citations
“…Since this is the first description of the use of a high dose of HIV DNA vaccine in NHP, we examined these two issues. In our recently published data, we clearly demonstrated that the great majority of primary cells transfected by our ⌬4SHIV KU2 DNA vaccine underwent apoptosis following the expression of viral proteins (4). Assuming that this mechanism also occurs in cells express- VOL.…”
Section: Fig 6 Hiv-specific Cd4mentioning
confidence: 65%
“…It will be interesting to evaluate whether such a route of immunization will help to reduce the amount of DNA given without altering the quantitative and qualitative characteristics of the induced IR. As an additional mechanism, using our HIV DNA construct we emphasized in a recent report the importance of induced cell death in the generation of Gagspecific CD8 ϩ T-cell responses (4). Such an event commonly is associated with electroporation methods (7,22,46,56,60), likely contributing to the cross-presentation of apoptotic bodies by DCs.…”
Section: Fig 6 Hiv-specific Cd4mentioning
confidence: 98%
See 1 more Smart Citation
“…It is tempting to suggest that efficient HIV Gag antigen presentation may need a higher level or longer time of antigen expression than other antigens. In support of this hypothesis, it has been shown that the immunogenicity of HIV-1 Gag generated by DNA vaccination can be more dependent on the formation of viral-like particles than other antigens (1). The results shown here suggest that rAd5-based vectors, especially Gag-encoding vectors, are less likely to stimulate HIV-1 immunity in an Ad5 seropositive population; such a suppressive effect may also have contributed to the lack of rAd5 vaccine efficacy in the recent STEP trial.…”
Section: Vol 84 2010mentioning
confidence: 91%
“…Chemokine receptors, YFP-tagged G␣ i subunits, and the Gq i5 chimera have been described (32)(33)(34)(35)(36). Mutations replacing each one of the three lysines at positions 296, 307, and 314 of G␣ i2 (but not in G␣ i3 ) with arginines were engineered by PCR mutagenesis of YFP-tagged G␣ i2 (35).…”
Section: Methodsmentioning
confidence: 99%